Experimental study of tribological properties of surface texture on rock bit sliding bearings. (December 2014) - Wang, GR; Zhong, L; He, X; Yang, QM; Yang, CH; Jiang, L
The influences of frictional characteristics of textured surface on rock bit sliding bearing have been investigated through unit experiments where the friction couple was equivalent to a pin-on-disc configuration. Cylindrical and elliptical textures are designed with different sizes, densities ratio and depths, fabricated using precision micro-mechanical engraving. Under the identical testing conditions in which the test force is 430 N and average linear velocity is 0.29 m/s, cylindrical texture with diameter of 300 µm, density ratio of 5.04%, and depth of 40 µm, exhibits lower friction coefficient, temperature rise and wear loss than that of untextured unit specimens. Friction coefficient decreased by 56.3%, similarly temperature rise decreased by 51.9%, and wear loss of textured disc specimens decreased by 52.9%. This study presents that the designed texture with relative small size and density ratio has obvious effect of lubrication and antifriction improvement compared with other specimens which has the same texture depth of 40 µm that it is approximately half of rock bearing radial clearance for rock bit sliding bearing under low-speed and high-load operating conditions.